DETECTABILITY OF PULMONARY TUBERCULOSIS IN SCHOOLCHILDREN FROM DIFFERENT REGIONS OF THE REPUBLIC OF TAJIKISTAN - U.YU. SIRODJIDINOVA; O.I. BOBOKHODJAEV; K.I. PIROV; F.S. SIRODJIDINOV (Паёми Сино, 2017)
Objective: To study the infection rate and latent forms of tuberculosis (TB) among the children of school age.